Question

Induction proofs. a. Prove by induction: n sum i^3 = [n^2][(n+1)^2]/4 i=1 Note: sum is intended...

Induction proofs. a. Prove by induction: n sum i^3 = [n^2][(n+1)^2]/4 i=1 Note: sum is intended to be the summation symbol, and ^ means what follows is an exponent b. Prove by induction: n^2 - n is even for any n >= 1 10 points 6) Given: T(1) = 2 T(N) = T(N-1) + 3, N>1 What would the value of T(10) be?

7) For the problem above, is there a formula I could use that could directly calculate T(N)?



8) Using induction, prove that your formula is correct.
0 0
Add a comment Improve this question Transcribed image text
Answer #1

a) n sum i^3 = n^2[(n+1)^2]/4

   Base case n = 1

   LHS:
      1 sum i^3 = 1

   RHS:
       1^2[(1+1)^2]/4 = 1

   Base case satisfied

   Now we assume for n = k it is true

   k sum i^3 = k^2[(k+1)^2]/4

   we will prove for n = k + 1

   (k+1) sum i^3 = (k+1)^2[(k+2)^2]/4
  
   Starting from LHS:

   for n = k+1 we have

    k^2[(k+1)^2]/4 + (k+1)^3

   = (k^2(k^2 + 2k + 1) + 4*(k^3 + 1 + 3k^2 + 3k))/4
   = (k^4 + 2k^3 + k^2 + 4k^3 + 4 + 12k^2 + 12k)/4
   = (k^4 + 6k^3 + 13k^2 + 12k + 4)/4

   RHS:
       (k^2 + 2k + 1)(k^2 + 4k + 4)/4
       (k^4 + 4k^3 + 4k^2 + 2k^3 + 8k^2 + 8k + k^2 + 4k + 4)/4
       (K^4 + 6k^3 + 13k^2 + 12k + 4)/4

   Hence proved

b) n^2 - n is even

   Base case n =1
  
   1 -1 = 0
   0 % 2 = 0

   Base case holds

   We assume for n = k

   k^2 - k is even

   we will prove for n = k+1

    (k+1)^2 - k-1 is even


   (k+1)^2 - k-1
   k^2 + 2k + 1 -k -1
   k^2 + k
   k^2 -k + 2k

   k^2-k is even and 2k is even. Sum of two even is even . Hence proved

----------------------------------------------------

   T(1) = 2
   T(N) = T(N-1) + 3

   We have the formula

   T(N) = ((N-1)*N)/2 +1 + 3(N-1)

   T(10) = (9 * 10)/2 + 2 = 47

   Base case N= 1

   T(1) = 0*1/2 +1 + 3*0 = 2
  
   Base case holds

   We assume for N= k
    T(k) = (k)*(k-1)/2 + 1 + 3(k-1)

   We will prove for N = k+1

    T(k+1) = (k+1) * (k)/2 + 1 + 3(k)


    T(k+1) = T(k) + 3 // As given in the question
           = (k + 1)*k/2 + 1 + 3(k-1) + 3
           = (k+1)*k/2 + 1 + 3k

    Hence Proved
        
   


  

Add a comment
Know the answer?
Add Answer to:
Induction proofs. a. Prove by induction: n sum i^3 = [n^2][(n+1)^2]/4 i=1 Note: sum is intended...
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for? Ask your own homework help question. Our experts will answer your question WITHIN MINUTES for Free.
Similar Homework Help Questions
ADVERTISEMENT
Free Homework Help App
Download From Google Play
Scan Your Homework
to Get Instant Free Answers
Need Online Homework Help?
Ask a Question
Get Answers For Free
Most questions answered within 3 hours.
ADVERTISEMENT
ADVERTISEMENT
ADVERTISEMENT